Regulation of adrenoceptor and muscarinic receptor gene expression after single and repeated stress - Myslivecek, Jaromir; Tillinger, Andrej; Novakova, Martina; Kvetnanský, Richard (Annals of the New York Academy of Sciences, 2008)
Although stress is tightly connected with elevated levels of catecholamines, stress effects on target structures of catecholamine action--adrenoceptors (ARs)--has not been deeply studied yet. Similarly, very little is known about changes of muscarinic receptors (MRs) during stress. We determined changes in these receptors in the individual parts of the heart (right atria and ventricles) of animals (rats and mice) exposed to a single and repeated immobilization stress. Changes of tissue catecholamines, beta(2)-AR gene expression, protein levels, and binding sites were determined in rat right ventricles, and changes in beta(1)-, beta(2)-, and beta(3)-AR gene expression were followed in murine right atria. Tissue catecholamines were elevated, while beta(2)-AR mRNA levels and beta(2)-AR proteins and binding were decreased, in rat right ventricles. In murine right atria, beta(1)- and beta(2)-AR gene expression was elevated, while beta(3)-AR mRNA levels and M(2)-MR were reduced. Taken together, our data show that interaction of AR and MR is important for the organism coping with stress and that different heart regions reveal distinct reactions to stress.
Keywords: Receptors, Adrenergic, beta; Gene Expression Regulation; radioligandová zkouška; srdeční komory; Protein Isoforms; RNA, Messenger; beta-adrenergní receptory; receptory muskarinové; Restraint, Physical; potkani Sprague-Dawley; Radioligand Assay; psychický stres; noradrenalin; Norepinephrine; protein - isoformy; fyzické omezení; srdeční síně; adrenalin; krysa rodu Rattus; Epinephrine; Animals; zvířata; regulace genové exprese; Stress, Psychological; Rats; myši inbrední C57BL; myši; Mice, Inbred C57BL; Heart Ventricles; Receptors, Muscarinic; Mice; messenger RNA; Heart Atria; Rats, Sprague-Dawley